The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11032-012-9779-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of two traditional Basmati rice varieties for bacterial blight resistance and plant stature through morphological and marker-assisted selection

Abstract: Bacterial blight (BB) is a major production threat to Basmati, the aromatic rice prized for its unique quality. In order to improve the BB resistance of two elite, traditional BB-susceptible Basmati varieties (Taraori Basmati and Basmati 386), we utilized the strategy of limited marker-assisted backcrossing Electronic supplementary material The online version of this article (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Most importantly, a very closely linked PCR-based marker, pTA248 is available for marker-assisted selection of the gene (Ronald et al 1992). Many earlier studies have shown that through marker-assisted breeding, Xa21 can be successfully introgressed into elite rice varieties (Joseph et al 2004;Gopalakrishnan et al 2008;Sundaram et al 2008Sundaram et al , 2009Perumalsamy et al 2010;Pandey et al 2013) and into hybrid rice parental lines (Chen et al 2001;Liyong et al 2003;Basavaraj et al 2010;Hari et al 2011Hari et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, a very closely linked PCR-based marker, pTA248 is available for marker-assisted selection of the gene (Ronald et al 1992). Many earlier studies have shown that through marker-assisted breeding, Xa21 can be successfully introgressed into elite rice varieties (Joseph et al 2004;Gopalakrishnan et al 2008;Sundaram et al 2008Sundaram et al , 2009Perumalsamy et al 2010;Pandey et al 2013) and into hybrid rice parental lines (Chen et al 2001;Liyong et al 2003;Basavaraj et al 2010;Hari et al 2011Hari et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of these genes give complete race-specific resistance to the pathogen. The genes have either been introgressed singly or pyramided in breeding for BLB resistance in rice [16]. Due to artificial and natural selection of BLB resistant genes, the bacterial races keep evolving.…”
Section: Genetic Basis Of Bacterial Leaf Blight Resistance In Ricementioning
confidence: 99%
“…Of these R genes, nine of the R genes have been cloned and characterized (Xa1, Xa3/Xa26, xa5, xa13, Xa10, Xa21, Xa23, xa25, and Xa27) encoding different types of proteins, suggesting multiple mechanisms of R-gene-mediated Xoo resistance [7,8,10,11,13,14,[19][20][21]. Most of these genes provide complete and race-specific resistance to Xoo and have been used singly or in combination in rice breeding for BB resistance [22][23][24][25][26][27][28][29][30][31][32]. Since the bacterial races tend to evolve continually, influenced by the artificial and natural selection of genes resistant to BB, it is required to explore critically the new resistant resources to combat the evolved races.…”
Section: Introductionmentioning
confidence: 99%